1.Wykonaj mnożenia.
a) -5(m-n)
b) -6(-c - d)
c)½(4x - 2)
d)-⅔(6a - 12b)
e)(c - 2d) * (-0,5)
f)(x² + 3y²) * (-1,2)

2.Wykonaj mnożenia.
a) - 4(3y - 4x)
b) 4 (a/₂ + b/₂)
c)2 (a² + 3b - 4x - 12)
d)-⅓ (6x³ - 12x² - 3x)
e) ¹/₄ (1,2xy² - 2y³ - 0,4y²)
f) 3 (4xy² - 3x²y - x³y - 3xy)

3.Usuń nawiasy i wykonaj redukcję wyrazów podobnych.
a) 3x - 4(y-3x)
b) 8(-12x + y) +12x
c)3(a - 3b) - 4(2b - 4x)
d) -5(4a - 3b) - 4(5a - 5b)
e) -2x(x - 5y - 3) + 3x(x + 5y + 2)
f)-3x(2x - 3y) + 2x(-3x - 5y - 1)

@Daje najlepsze

3

Odpowiedzi

2009-11-17T21:30:47+01:00
1
a)=-5m-5n
b)=6c+6d
c)=2x-1
d)=-4a+8b
e)=-1/2c+1d
f)=-12/10x²-36/10y²
2
a)=-12y+16x
b)=2a+2b
c)=2a²+6b-8x-24
d)=-2x³+4x²+x
e)=12/40xy²-1/2y³-1/10y²
f)=12xy²-9x²y-3x³y-9xy
3
a)=3x-4y+12x=15x-4y
b)=8*(-12x+y)+12x=-96x+8y+12x=-84x+8y
c)=3a-6b-8b+16x=3a-14b+16x
d)=-20a+15b-20a+20b=-40a+35b
e)=-2x²+10xy+6x+3x²+15xy+6x=x²+25xy+12x
f)=-6x²+9xy-6x²-10xy-2x=-12x²-xy-2x
Najlepsza Odpowiedź!
2009-11-17T21:36:57+01:00
1

a) -5(m-n)=-5m+5n
b) -6(-c - d)=6c+6d
c)½(4x - 2)=2x-1
d)-⅔(6a - 12b)= -4a+8b
e)(c - 2d) * (-0,5)= -0,5c+d
f)(x² + 3y²) * (-1,2)= -1,2x²- 3,6y²

2

- 4(3y - 4x)=-12y+16x
b) 4 (a/₂ + b/₂)= 4a/z+4b/z
c)2 (a² + 3b - 4x - 12)= 2a²+6b-8x-24
d)-⅓ (6x³ - 12x² - 3x)= -2x³+4x²+x
e) ¹/₄ (1,2xy² - 2y³ - 0,4y²)=0,3xy²-0,5y³-0,1y²
f) 3 (4xy² - 3x²y - x³y - 3xy)= 12xy²-9x²y-3x³y-9xy

3
a) 3x - 4(y-3x)=3x-4y+4x=7x-4y
b) 8(-12x + y) +12x= -96x+8y+12x=-84x+8y
c)3(a - 3b) - 4(2b - 4x)= 3a-9b-8b+16x=3a-17b+16x
d) -5(4a - 3b) - 4(5a - 5b)= -20a+15b-20a+20b=-40a+35b
e) -2x(x - 5y - 3) + 3x(x + 5y + 2)=-2x²+10xy+6x+3x²+15xy+6x=x²+25xy+12x
f)-3x(2x - 3y) + 2x(-3x - 5y - 1)= -6x²+9xy-6x²-10xy-2x=-12x²-xy-2x
1 5 1
2009-11-17T21:40:13+01:00
1.
a. -5m + 5n
b. 6c + 6d
c. 2x-1
d. -4a + 8b
e. -0,5x + d
f. -1,2x² - 3,6y²
2.
a. -12y + 16x
b. 4a/z + 4 b/z
c. 2a² + 6b - 8x - 24
d. -2x³ + 4x² + x
e. 3/10xy² - 1/2y³ - 1/10y²
f. 12xy² - 9x²y - 3x³y - 9xy
3.
a. 3x-4y+12x
15x-4y
b.-96x + 8y + 12x = -84 + 8y
c.3a -9b - 8b + 16x = 3a - 17b +16x
d. -20a + 15b -20a +20b = 35b
e. -2x² +10xy +6x +3x² + 15xy + 6x =x² + 25xy + 12x
f. -6x² - 9xy - 6x² -10xy - 2x= -12x² - 19xy - 2x